2012
DOI: 10.1016/j.ijid.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors predictive of the prognosis in Crimean-Congo hemorrhagic fever: new suggestions

Abstract: It is essential to determine the possibility of a fatal prognosis in CCHF patients using clinical history and biochemical parameters so that the necessary precautions can be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 12 publications
(23 reference statements)
6
30
1
2
Order By: Relevance
“…Even though the CRP level is not usually elevated in viral diseases, an elevated CRP level has been reported in some viral diseases (17). It has also been reported that the CRP level is higher in fatal cases than in non-fatal ones in CCHF (15,18). Similarly, in our study, the CRP level was high in all patients, but it was higher in fatal than in non-fatal patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Even though the CRP level is not usually elevated in viral diseases, an elevated CRP level has been reported in some viral diseases (17). It has also been reported that the CRP level is higher in fatal cases than in non-fatal ones in CCHF (15,18). Similarly, in our study, the CRP level was high in all patients, but it was higher in fatal than in non-fatal patients.…”
Section: Discussionsupporting
confidence: 61%
“…Elevated liver enzymes, prolonged bleeding time, and decreased platelet and leukocyte levels have been observed in many studies (11)(12)(13)(14)(15). In most of these studies, majority of these parameters were found to be related to the prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…With the first patient, who was the first losing her baby, we noticed that she had hypotension and very low levels of fibrinogen [12]. Maybe low levels of fibrinogen are prognostic factors, especially in hemorrhagic fever of Crime-Congo [13].…”
Section: Discussionmentioning
confidence: 96%
“…KKKA'nın tipik laboratuvar bulguları, trombositopeni, lökopeni, aspartat aminotransferaz (AST), alanin aminotransferaz (ALT), kreatin kinaz (CK) ve laktat dehidrogenaz (LDH) düzeylerinin yükselmesidir (6,7). Hastamızda ilk günkü hemogram, AST, ALT, LDH ve CK değerleri normal sınırlar-daydı.…”
Section: İrdelemeunclassified
“…KKKA'da tanı, hastamızda da olduğu gibi, özgül IgM ve IgG antikorlarının PCR ile saptanmasıyla konulmaktadır (6,8).…”
Section: İrdelemeunclassified